2020
DOI: 10.4149/bll_2020_032
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of betanin and copper on heart and lung in end‑organ ischemia reperfusion injury

Abstract: OBJECTIVES: Betanin and copper sulphate have been previously indicated as benefi cial agents for ischemia/reperfusion (I/R) as antioxidant compounds in various models. We investigated whether betanin and copper have any protective effects on the heart and lung against I/R injury in rats. METHODS: Spraque-Dawley rats were assigned in groups: Sham (laparotomy only), control (I/R only), betanin treatment (100 mg/kg of betanin administered intraperitoneally (i.p.) 60 minutes before I/R) and copper sulfate treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Betanin prevents oxidative damage in the lung and heart of animals induced by ischemia-reperfusion injury, evidenced by decreased MDA production in tissues. The same favorable effect of betanin on MDA was observed in the abdominal aorta following ischemia and reperfusion injury (Tural et al 2020a;2020b). Taken together, these findings reinforce the protective effects of betanin on vascular integrity against oxidative damage.…”
Section: Betanin Atherogenesis and Cardiovascular Diseasessupporting
confidence: 75%
“…Betanin prevents oxidative damage in the lung and heart of animals induced by ischemia-reperfusion injury, evidenced by decreased MDA production in tissues. The same favorable effect of betanin on MDA was observed in the abdominal aorta following ischemia and reperfusion injury (Tural et al 2020a;2020b). Taken together, these findings reinforce the protective effects of betanin on vascular integrity against oxidative damage.…”
Section: Betanin Atherogenesis and Cardiovascular Diseasessupporting
confidence: 75%
“…On the contrary, the normalization of the blood pressure was attained in rat myocardium due to the pretreatment of BTA. [21][22][23] It has been reported that in chronic heart disease, accumulated reactive oxygen species due to reduced activity of anti-oxidant enzymes trigger the oxidative stress and results in cardiac necrosis. 24,25 ROS would cause peroxidation of lipids and proteins into advanced glycation end products (AGEs) and its deposition on the cardiac tissues on circulation would cause changes in the heart structure and results in damage to the cardiac tissues fibrils and weakening of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The MDA level is an end-product of lipid peroxidation at the end of the reperfusion process and an indication of increased free radical production [14]. MDA has been an important biochemical parameter measured in many experimental animal studies to evaluate the oxidative stress level [15].…”
Section: Malondialdehyde (Mda) Measurementmentioning
confidence: 99%